Cerebral near-infrared spectroscopy guided neonatal intensive care management for the preterm infant - Pellicer, A; de Boode, W; Dempsey, E; Greisen, G; Mintzer, J; Naulaers, G; Pichler, G; Roehr, CC; Roll, C; Schwarz, C; da Costa, CS; Kooi, E; et al. (Springer Nature, 2024)
Infants requiring admission to the neonatal intensive care unit (NICU) are particularly vulnerable to developing brain injury. The severity of the underlying clinical conditions and the complexity of care call for continuous, cot-side, non-invasive monitoring tools. Near-infrared spectroscopy (NIRS) measures the regional tissue oxygen saturation of hemoglobin (rStO2) and provides continuous information on the net-result of several factors. Cerebral rStO2 correlates with echocardiography-derived measures of blood flow. Cerebral fractional tissue oxygen extraction provides information on the balance between oxygen supply and demand and can be continuously derived from the combined use of cerebral rStO2 and arterial oxygen saturation. Information on cerebral blood flow autoregulatory capacity can be obtained from combining cerebral rStO2 and invasive blood pressure monitoring by appropriate software. Cerebral rStO2 provides real-time, end-organ information on perfusion-oxygenation, and when interpreted in the clinical context based on pathophysiological principles may be used as a help to guide interventions in the NICU. In this review we will discuss how to optimize NIRS monitoring for application in the NICU, with a particular focus on the preterm infant. Impact Near-infrared spectroscopy (NIRS) provides cot-side, real-time information on blood and oxygen supply to the brain. Therefore, it is a valuable tool to better understand the pathophysiology underlaying disease processes. - Current evidence suggests that NIRS-guided treatment in extremely preterm infants during transitional circulation does not improve clinical outcomes. - Specific training is needed to maximize potential performance. - Pathophysiological interpretation of cerebral NIRS data in the given clinical context may help in decision-making. - Appropriate use of this monitoring technique, interpreted concurrently with other routine parameters, is a potential clinical tool to guide interventions in the NICU setting.